(untitled) (Journal of Organizational Psychology, 2022)
Quality of care continues to be of serious concern in the United States. Part of addressing this concern must include academic programs that produce students with an appreciation of quality management to take up positions in healthcare organizations. Moreover, healthcare organizations must ensure that quality and safety are front of mind for those they employ, especially those in management. This study presents an evaluation of student perception of their readiness to work as part of quality management teams and undertake quality management activities. Majority of the students surveyed agreed that they felt well prepared to participate on a healthcare quality management (QM) team, felt confident in their ability to participate in QM activities, and were extremely confident in their QM skills. Additionally, majority of the respondent indicated that “everyone” was responsible for ensuring quality in the healthcare organization. Healthcare organizations must invest in the professional development of their employees especially in quality management. This may prove to be beneficial to their patients and bottom line.